DETECTION OF METHICILLIN-SENSITIVE STAPHYLOCOCCUS AUREUS AND METHICILLIN-RESISTANT STAPHYLOCOCCUS AUREUS IN THE INTENSIVE CARE UNIT OF PURI RAHARJA HOSPITAL - Widianantara, Made; Budayanti, Ni Nyoman Sri; Fatmawati, Ni Nengah Dwi; Hendrayana, Made Agus (E-Jurnal Medika Udayana; Vol 10 No 12 (2021): Vol 10 No 12(2021): E-Jurnal Medika Udayana, 2021)
Health care-associated infections (HAIs) are infections caused by microorganisms found in health care centers. Intensive Care Unit (ICU) patients are the population that most frequently infected with HAIs. One of the most common microorganisms that cause HAIs is Staphylococcus aureus. Methicillin-resistant Staplylococcus aureus (MRSA) is a strain of Staphylococcus aureus that is resistant to ?-lactam. Methicillin-sensitive Staphylococcus aureus (MSSA) and MRSA that contaminate medical equipments, including in the ICU, are the causes of HAIs. Therefore, research must be done to determine the levels of bacterial contamination on medical equipments and objects in the hospital ward. This study aimed to detect MSSA and MRSA in the ICU of Puri Raharja Hospital. This study was a descriptive study with a observational study design. The research population was the environmental surfaces in Puri Raharja Hospital environment. The samples in this study were 30 environmental surfaces in the ICU at Puri Raharja Hospital in the form of bed rails, tables, curtains, door handles, and stethoscopes that met the research criteria. The total number of samples used in this study were thirty that selected by total sampling technique. Samples were taken using sterile cotton swabs and then inoculated on Staphyococcus medium. Colonies were then tested by using catalase and coagulase tests to identify Staphylococcus aureus. Cefoxitin screen test showed that 1 out of 30 (3.33%) samples positive for MRSA. This study shows that there is MRSA contamination in one of the bed rails at Puri Raharja Hospital’s ICU. Keywords : Methicillin-resistant staphylococcus aureus, Intensive care unit, Health care-associated infections